2019
DOI: 10.1039/c9nj01619h
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacteria associated with stingless bees biosynthesize bioactive polyketides against bacterial pathogens

Abstract: Strong activity against the bacteria Paenibacillus larvae ATCC9545, the causative agent of the American Foulbrood disease of honey bees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 44 publications
1
28
0
3
Order By: Relevance
“…The compounds presented variable levels of activities against P. larvae. Compounds 28 and 30 showed the higher antibacterial activity, better than the control antibiotics [91]. Finally, two new compounds were isolated from Streptomyces sp.…”
Section: Natural Products Mediating Microbial Symbiosis In Stingless mentioning
confidence: 98%
“…The compounds presented variable levels of activities against P. larvae. Compounds 28 and 30 showed the higher antibacterial activity, better than the control antibiotics [91]. Finally, two new compounds were isolated from Streptomyces sp.…”
Section: Natural Products Mediating Microbial Symbiosis In Stingless mentioning
confidence: 98%
“…1D; Heine et al ., 2018) and in the heads of other ants (Liu et al ., 2018). Actinobacteria are also present in the bodies of stingless bees (Rodríguez‐Hernández et al ., 2019), wasps (Madden et al ., 2013) and termites (Sujada, Sungthong & Lumyong, 2014; Chouvenc et al ., 2018; Krishanti et al ., 2018), which produce antimicrobial secretions. Microbial natural products represent an important source for the discovery of potential new antibiotics, with actinomycetes being one of the most prolific groups that produce bioactive compounds (Genilloud, 2018; Niu, 2018).…”
Section: Social Insect Traits and Their Relevance To Ecosystem Servicmentioning
confidence: 99%
“…Whether this compound could attract bees and thus participate in mediating mutual interactions thus remains to be verified. Geosmin is an ecologically relevant compound eliciting either attraction or repulsion in a number of arthropod species including flies (Becher et al, 2010;Stensmyr et al, 2012), mosquitoes (Rodríguez-Hernández et al, 2019) and springtails (Becher et al, 2020). Although its ecological function remains mysterious in the case of honey bees, our data suggest that it may be equally relevant for this important pollinator, and worth investigating further.…”
Section: Behavioural Effectsmentioning
confidence: 79%
“…), protozoa, moulds and fungi (Gerber and Lechevalier, 1965;Liato and Aïder, 2017). Actinobacteria (including Streptomyces) are widely associated with hymenopteran nests, which they likely protect from pathogens thanks to their natural production of antibiotics (Madden et al, 2013;Matarrita-Carranza et al, 2017;Rodríguez-Hernández et al, 2019). A recent study found that fire ant queens (S. invicta) preferentially started new nests in actinobacteria-rich soil.…”
Section: Introductionmentioning
confidence: 99%